Résultat enquête - Ouoro, Justin; Palm-Sanou, Valentine; Fendler, Ute (De 2000 à 2020, Deux Décennies de Films de Fiction Burkinabè: Acteurs/Actrices, Orientations Thématiques et Profils Esthétiques, 2022)
Audience survey report; according to the improvements to be made in Burkinabe cinema in the 2000s
Keywords: Actors; Aesthetics; Experience; Cinema